Immunogenicity of inactivated COVID-19 vaccines at different vaccination intervals - Juan Li; Weixin Chen; Meng Chen; Shuang Bai; Qianli Yuan; Jiang Wu (Human Vaccines & Immunotherapeutics, 2021)
To evaluate the immunogenicity of inactivated COVID-19 vaccines administered at different intervals. Subjects who had received two doses of inactivated COVID-19 vaccines at an interval of 21 days or 1–7 months were selected to collect 5 ml of venous blood after the second dose for the detection of specific IgG antibody against SARS-CoV-2 using the chemiluminescent immunoassay. Blood samples were collected from 348 and 174 individuals vaccinated at an interval of 21 days or 1–7 months, respectively. Seropositive rate 2 weeks after two doses of vaccination at 21-days and 1–7 months interval was 95.7% and 97.1%, respectively, with no statistically significant difference. The post-vaccination antibody level was 23.7 with 21-days interval, higher than 14.2 with 1–7 months interval. Among the individuals vaccinated with two doses more than 1-month apart, seropositive rate was 98.5%, 90.0%, 91.7%, and 100% with 1- month (1–2 months, 2 months was not included, the same below), 2- month, 3- month, and 4–7 months of interval, respectively, and no statistically significant difference was observed. Appropriate extension of the vaccination interval between two doses of inactivated COVID-19 vaccine does not affect the production of specific IgG antibodies. The inactivated COVID-19 vaccine should be administered in accordance with the recommended vaccination schedule, and the vaccination interval can be extended appropriately under special circumstances.